Borate-modified carbon dots as a probe for quercetin in plants. Issue 2 (12th November 2020) - Gao, Mei; He, Man; Xing, Rang; Wang, Xuefei; Wang, Zhuo
Abstract : Schematic presentation of the PBA-CDs enhancing the fluorescence of quercetin in contrast to N-CDs. Abstract : Quercetin has been proved to have high medicinal value, and as a type of flavonol, has been found in many plants. A simple, fast and effective detection of quercetin was developed according to the fluorescence enhancement by modified carbon dots (PBA-CDs). PBA-CDs were prepared by connecting phenylboronic acids (PBA) on the surface of carbon dots rich in amino groups. Due to the selective interactions of PBA with the cis -diol groups of quercetin and the additional hydrogen bonds, the intermolecular rotation of quercetin was inhibited, and then the fluorescence significantly increased. The selectivity of this method was proved and the linear ranges were estimated to be 0–28.5 μM with a limit of detection at 28.8 nM. Using this method, the quercetin content in the Ginkgo biloba leaf was measured as 42.28 mg·g −1 . In addition, the PBA-CDs hold excellent biocompatibility and have demonstrated their ability to detect quercetin in living cells.